Dune Field Patterns and Their Control Factors in the Middle Areas of China’s Hexi Corridor Desert - Zhang, Yan; Zhang, Zhengcai (Frontiers in Earth Science, 2022)
The middle areas of China’s Hexi Corridor Desert are distributed within or at the edge of oases in continental river basins in Northern China. Recently, researchers found that rivers can provide sediment material for dune formation and development, but the mechanism has not been investigated in detail. In this study, the relationships among the wind environment, spatial distribution of continental rivers, sand availability, and dune field patterns in the middle area of Hexi Corridor Desert were analyzed. In terms of the wind energy environment, the study area can be divided into three regions: high-energy environment in the north, intermediate-energy environment in the middle, and low-energy environment in the south. The results showed that the resultant drift potential is predominantly from the NW quadrant. The directional variability of wind is intermediate in the northern and middle region and low in the southern region. The directions of winds with critical speed are SW in the northern region, NW and WNW in the middle region, and NW in the southern region. The main dune types are barchans, reticulate dunes, star dunes, linear dunes, and coppice dunes, which differ from previous results (mainly barchans and coppice dunes). Dune field patterns are controlled by the wind energy environment. In addition, the spatial distribution of continental rivers and sand availability are important factors affecting dune formation and development. Sand dunes are distributed downwind of continental rivers, which confirms the hypothesis that rivers can provide sediment material for dune formation. The spatial distribution and different dune types in the middle area of Hexi Corridor Desert reveal that their formation and development are controlled by the wind regime and sediment supply.